Role of resistance physical exercise in preventing testicular damage caused by chronic ethanol consumption in UChB rats - Dutra Gonçalves, Gessica; Antunes Vieira, Nichelle; Rodrigues Vieira, Henrique; Dias Valério, Aline; Elóisa Munhoz de Lion Siervo, Gláucia; Fernanda Felipe Pinheiro, Patricia [UNESP]; Eduardo Martinez, Francisco [UNESP]; Alessandra Guarnier, Flávia; Rampazzo Teixeira, Giovana [UNESP]; Scantamburlo Alves Fernandes, Glaura (Wiley, 2017)
Ethanol consumption is associated with spermatogenesis damage and testosterone level alterations. Alcohol remains the most commonly used substance among athletes and sports enthusiasts. This study evaluated whether resistance physical exercise can reduce the testicular damage caused by ethanol exposure. A total of 36 ethanol drinking (UChB) rats were divided into four groups: C (control rats), ETOH (ethanol consumption), ETOH + T (ethanol consumption + physical training), and T (group physical training). The physical training component of the T and ETOH + T groups was based on a resistance training model consisting of four sets of 10 jumps, with an increasing overload of 50–70% of the body weight attached to the chest three times per week. Rats in the ETOH and ETOH +T groups received 10% ethanol. At postnatal day 90, the rats were sacrificed. Blood sample was collected for hormonal analysis, and the testicles were weighed and processed for histopathological, morphometric, and immunohistochemical analyses. The ETOH group showed an increase in testosterone levels. The immunohistochemical of androgen receptor and the absolute weight of the testes were higher in the ETOH and ETOH + T groups, while the ETOH animals showed a decreased weight gain index. The number of abnormal seminiferous tubules increased in the ETOH and T groups compared to those in the control group (C); however, the association with treatment (ETOH + T group) prevented this effect and decreased caspase-3 production. In conclusion, these findings show that the combination of ethanol consumption and resistance physical exercise can prevent testicular damage in adult UChB rats.
Keywords: ethanol; resistance physical exercise; testes; UChB rats